Conversion rate of tuberculosis screening tests among dermatology patients treated with tumor necrosis factor inhibitors - Sarah F Alsukait; Alaa B Alsaad; Ghadah F Alotaibi; Fahad M Alsaif; Hend M Alotaibi (Wolters Kluwer Medknow Publications, 2022)
Background: The use of tumor necrosis factor-α inhibitors (TNFi) has been associated with an increased risk latent tuberculosis (TB) reactivation. The role of TB screening assays in monitoring patients during TNFi therapy remains uncertain. Spontaneous conversions and reversions have been described. Aims: This study aims to determine the conversion and reversion rate of TB screening tests among dermatology patients receiving TNFi in a country with moderate TB incidence. Subjects and Methods: A retrospective single-center study conducted on all patients in whom treatment with TNFi was initiated in our dermatology clinic in a tertiary university hospital, Riyadh, Saudi Arabia, until September 2018. Data were collected from the hospital electronic patient information system. Results: One hundred and eighteen patients were included. Majority (79.9%) of patients used adalimumab. Psoriasis was the most common indication (90%). Among patients with negative baseline TB screening who had been retested during TNFi therapy (n = 65; 55%), conversion to positive was observed in nine patients (13.8%) with a mean duration of exposure of 39.7 months, whereas among patients with positive TB testing result (n = 18), 10 (55.5%) reverted to negative. Conclusions: This study emphasizes the need for prospective large-scale multispecialty studies assessing the significance of TB retesting, which should be considered when designing rescreening protocols.